ʼPhags ma Sgrol-ma la gsol gdab mchod pa maṇḍal bźi bar grags paʼi cho ga ʼdod don yid bźan ʼgrub paʼi ljon śiṅ bźugs - Si-tu Paṇ-chen Chos-kyi-ʼbyuṅ-gnas, 1699 or 1700-1774 (s.n., 1969)
Method for the propitiation of Tara, Buddhist deity, through the offering of the mandala, includes a petition to the teachers in the transmission lineage.